Online Documentation Portals in Library Technical Services: Shedding Light on Local Practices and Procedures - Craft, Anna R. (Serials review, 2019)
The creation, sharing, and maintenance of documentation are critical to support the often detailed and complex work of library technical services units. This column examines documentation portals that share technical services policies and procedures, with a focus on library-based portals that are accessible to personnel within the associated libraries while also being fully or partially open to external users. A review of the literature is provided, as well as links to and descriptions of selected portal examples.